Anti-HBV treatment partially restores the dysfunction of innate immune cells and unconventional T cells during chronic HBV infection - Shu, Yiwen; Li, Sumeng; Du, Yanqin; Zheng, Xin (Frontiers in Immunology, 2025)
Despite the successful implementation of prophylactic vaccines, hepatitis B virus (HBV) continues to affect over 350 million individuals globally. It remains a predominant etiology of end-stage liver pathologies, including liver cirrhosis and hepatocellular carcinoma (HCC). While nucleos(t)ide analog (NUC) therapies effectively suppress viral replication, functional cure is achieved in less than 1% of patients annually. Given that viral clearance fundamentally requires reconstitution of antiviral immunity, emerging therapeutic paradigms necessitate combinatorial strategies integrating direct-acting antiviral agents with immunomodulatory interventions. Substantial research efforts have been directed toward elucidating the immunological mechanisms underlying HBV persistence during chronic infection. This review systematically summarizes the functional impairment of innate immune populations and unconventional T cell subsets across distinct clinical phases of chronic HBV infection, and characterizes longitudinal immune reconstitution patterns following antiviral treatments. Our review identifies potential immunological biomarkers and provides a mechanistic framework for developing targeted immunotherapies to achieve durable HBV control.